‘Van den vleeschouweren oft pensvrouwen’* De economische mogelijkheden voor vrouwen in het Leuvense vleeshouwersambacht in de vijftiende en zestiende eeuw - Vandeweerdt, Nena (TSEG - The Low Countries Journal of Social and Economic History, 2018)
Women’s economic activity in the butcher’s guild of fifteenth and sixteenth-century LeuvenThis article examines women’s agency in the butchers’ guild in Leuven during the fifteenth and sixteenth centuries. An analysis of urban ordinances demonstrates that the corporation allowed women of various marital status to work in the trade. Married women acted frequently as active substitutes of their husbands or as part of a family production unit. Unmarried women, most often widows, were allowed to perform certain tasks independently. This contrasts with findings in earlier studies about gendering in butchers’ guilds in other towns. I argue that the changing hereditary character of the corporation influenced women’s agency in the trade.